2020
DOI: 10.1002/iid3.294
|View full text |Cite
|
Sign up to set email alerts
|

Changes in passively‐sensitized basophil activation to αS1‐casein after oral immunotherapy

Abstract: Introduction: Immune response to cow's milk allergen (CMA) has been analyzed mostly using crude milk antigen or a mixture of various caseins. This study aimed to assess the changes in the immunological response against αS1-casein during oral immunotherapy (OIT) and to investigate the mechanism of tolerance. Methods: We have performed rush OIT to 39 patients with CMA and obtained the serum samples up to 3 years after OIT. Immunoglobulin E (IgE) and IgG4 antibodies specific to highly purified αS1-casein as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…This study used serum from 39 patients [median age 8 years (IQR 6-10 years)], from a previous study, with persistent CM allergy before oral immunotherapy. 4,8 These patients were required to have retained their milk allergy over age 5 with the threshold dose less than 5 mL of CM confirmed by an oral food challenge test, and detectable specific IgE (>0.34 UA/mL) to CM and whole CN by ImmunoCAP ® .…”
Section: Serum Samplesmentioning
confidence: 99%
“…This study used serum from 39 patients [median age 8 years (IQR 6-10 years)], from a previous study, with persistent CM allergy before oral immunotherapy. 4,8 These patients were required to have retained their milk allergy over age 5 with the threshold dose less than 5 mL of CM confirmed by an oral food challenge test, and detectable specific IgE (>0.34 UA/mL) to CM and whole CN by ImmunoCAP ® .…”
Section: Serum Samplesmentioning
confidence: 99%
“…4,5 With respect to BATs using components, it is noteworthy that a single component rarely covers the entire sensitization profile, 79,80 and that outcomes have been reported to be age and/or population dependent. 74 BATs have also been used to monitor AIT and allergen-specific oral immunotherapy for peanut, 57,[81][82][83] sesame, 84 cow's milk, [85][86][87] and egg. 88 In line with the findings for aeroallergens, reduced basophil allergen sensitivity during AIT and oral immunotherapy with food is likely due to interference of blocking sIgG antibodies.…”
Section: Food Allergymentioning
confidence: 99%
“…88 In line with the findings for aeroallergens, reduced basophil allergen sensitivity during AIT and oral immunotherapy with food is likely due to interference of blocking sIgG antibodies. [81][82][83][84]87,88 Acosta et al 89 recently provided an immunologic explanation as to why birch-associated apple allergy cannot be effectively treated by administration of the sensitizing pollen allergen (sublingual immunotherapy with recombinant Betula verrucosa 1, the major allergen from birch Betula verrucosa]). They found that treatment with recombinant Betula verrucosa 1 promotes specific IgG antibodies that cross-react with recombinant Malus domesticus 1 from apple but lack sufficient affinity to inhibit BATs with apple allergens and induce cross-protection.…”
Section: Food Allergymentioning
confidence: 99%
“…This study used serum from 39 patients [median age 8 years (IQR 6-10 years)], from a previous study, with persistent CM allergy before oral immunotherapy. 4,7 These patients were required to have retained their milk allergy over age 5 with the threshold dose less than 5 mL of CM confirmed by an oral food challenge test, and detectable specific IgE to CM and whole CN by ImmunoCAP ® .…”
Section: Serum Samplesmentioning
confidence: 99%